Investigating the Intention to Use an Electronic Performance Management System at XYZ Holdings Limited: Towards a Revised Technology Acceptance Model - Joomunbaccus, Sheran (Archives of Business Research, 2021)
This paper investigates the intention to use an electronic Performance Management System (e-PMS) through a conceptual framework derived from the Technology Acceptance Model where several constructs were put under investigation. The positivist approach was adopted in view of collecting primary data from a sample of 52 employees working at XYZ Holdings Limited through a structured survey questionnaire comprising of 25 items segregated under 6 sections. Research findings revealed a positive individual relationship between each independent variable; perceived usefulness, perceived ease of use, attitude and accessibility with intention to use the e-PMS respectively. Gender, age, grade and working experience were found to be statistically insignificant. However, when analyzing the constructs simultaneously as a whole model, only perceived ease of use and attitude were found to be statistically significant towards the intention to use the software. The derived model will be useful not only to the management of XYZ Holdings Limited but also to other companies which intend to adopt a new technology while at the same time serves as a base for future research in this field.